2013
DOI: 10.2147/ijn.s45821
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of 5-aminolevulinic acid (ALA) loaded PLGA nanoparticles

Abstract: Background: 5-Aminolevulinic acid (ALA) is a prodrug for topical photodynamic therapy. The effectiveness of topical ALA can be limited by its bioavailability. The aim of this study was to develop a novel ALA delivery approach using poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs). Methods: A modified double emulsion solvent evaporation method was used to prepare ALA loaded PLGA NPs (ALA PLGA NPs). The characteristics, uptake, protoporphyrin IX fluorescence kinetics, and cytotoxicity of ALA PLGA NPs tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 33 publications
0
42
0
1
Order By: Relevance
“…The major reasoning is that increased lipophilicity potentially improves the passage through biological membranes thus increasing intracellular substrate concentration for heme biosynthesis. Recently, substantial efforts have also been directed towards nanocarriers loaded [20][21][22][23][24] or conjugated [25][26][27][28] with 5-ALA. These approaches tackle some of the pharmacokinetic and specificity drawbacks of 5-ALA but have so far failed to produce a clinical candidate for the improved delivery of 5-ALA mostly due to high 5-ALA loading and delivery required for this type of FPD or PDT.…”
Section: Introductionmentioning
confidence: 99%
“…The major reasoning is that increased lipophilicity potentially improves the passage through biological membranes thus increasing intracellular substrate concentration for heme biosynthesis. Recently, substantial efforts have also been directed towards nanocarriers loaded [20][21][22][23][24] or conjugated [25][26][27][28] with 5-ALA. These approaches tackle some of the pharmacokinetic and specificity drawbacks of 5-ALA but have so far failed to produce a clinical candidate for the improved delivery of 5-ALA mostly due to high 5-ALA loading and delivery required for this type of FPD or PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the encapsulation of photosensitizers in polymeric nanoparticles of poly(lactic-co-glycolic) acid (PLGA) increases the efficiency of photosensitizers in reducing the viability of cancer cells. PLGA is a biomaterial, biodegradable with good biocompatibility and stability, developed in the 1970s and approved by the United States Food and Drug Administration (FDA) for drug delivery (Shi et al, 2013). Ricci-Junior and Marchetti (2006) demonstrated that zinc phthalocyanine is more efficient in reducing the viability of lymphoid lineage P388D1 neoplastic cells.…”
Section: Introdutionmentioning
confidence: 99%
“…7 Our in vitro study suggested that the use of polylactic-co-glycolic acid (PLGA) NPs could improve ALA delivery in human cutaneous SCC cells. 8 The aim of this in vivo study was to evaluate the feasibility of ALA PLGA NP-mediated PDT for the treatment of cutaneous SCC in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…8 The examination of in situ PpIX-fluorescence kinetics showed that SCCs incubated with ALA PLGA NPs generated higher levels of PpIX than those incubated with free ALA of the same concentration ( Figure 2). This is possibly because free ALA might be directly dissolved in the extracellular compartment and decompose, whereas PLGA NPs could protect ALA from such degradation.…”
mentioning
confidence: 97%
See 1 more Smart Citation